Students’ interest in entrepreneurship: A case study of ‘Business Day’/ Suhanom Mohd Zaki, Norulhuda Tajuddin and Mas'udah Asmui - Mohd Zaki, Suhanom; Tajuddin, Norulhuda; Asmui, Mas'udah (Unit Penerbitan Universiti (JAPENA), 2016)
A lot of effort has been made to increase students’ interest in entrepreneurship in Malaysian higher learning institutions. As a result, students are more confident to manage their own business with the help and support from university which provides various entrepreneurship programme. Therefore, Faculty of Business Management of Universiti Teknologi Mara (UiTM) Pahang held an event called ‘Business Day’for students who were enrolled in Creative and Critical Thinking course (MGT315). During the event, students were divided into a few groups and asked to sell various items in one day. Through this event, students were given exposure on how to manage business which included marketing, choosing products and financial management. A small portion of the profit made was donated to Projek Iqra’. This paper aims to study students’ attitudes and perceptions on ‘Business Day’. All students enrolled in MGT315 were involved as respondents and a set of questionnaire which was specially tailored for the study was used as a research instrument. Simple statistics study was used to explain students’ attitudes and perceptions on the event. Results show that students were already interested in entrepreneurship and their interest grew after the event. Findings also show that ‘Business Day’ managed to increase students’ level of confidence and change their perception to choose entrepreneurship as a career in future.